2015
DOI: 10.1371/journal.pone.0118913
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Active Metabolites Produced by the Basidiomycete Quambalaria cyanescens

Abstract: Four strains of the fungus Quambalaria cyanescens (Basidiomycota: Microstromatales), were used for the determination of secondary metabolites production and their antimicrobial and biological activities. A new naphthoquinone named quambalarine A, (S)-(+)-3-(5-ethyl-tetrahydrofuran-2-yliden)-5,7,8-trihydroxy-2-oxo-1,4-naphthoquinone (1), together with two known naphthoquinones, 3-hexanoyl-2,5,7,8-tetrahydroxy-1,4-naphthoquinone (named here as quambalarine B, 2) and mompain, 2,5,7,8-tetrahydroxy-1,4-naphthoquino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 31 publications
(36 reference statements)
2
36
0
Order By: Relevance
“…Stodulkova et al . [ 13 ] described a novel active metabolite naphthoquinone (quambalarine A) with broad antifungal and antibacterial activity from Q . cyanescens .…”
Section: Introductionmentioning
confidence: 99%
“…Stodulkova et al . [ 13 ] described a novel active metabolite naphthoquinone (quambalarine A) with broad antifungal and antibacterial activity from Q . cyanescens .…”
Section: Introductionmentioning
confidence: 99%
“…This assay is based on the dye CellROX Green which is a fluorogenic probe used for measuring oxidative stress in live cells (Cheloni, Cosio & Slaveykova, 2014). The dye is weakly fluorescent inside cells in a reduced state but exhibits bright green photostable fluorescence upon oxidation by ROS and subsequent binding to DNA (Gemelli et al, 2014; Stodůlková et al, 2015). Modifications to the procedure recommended by the supplier were made as described in Material and Methods in order to detect ROS positive B. braunii  colonies.…”
Section: Resultsmentioning
confidence: 99%
“…Quambalaria cyanescens has further been reported as a symbiont of plants. Recently, few studies have reported broad-spectrum antimicrobial activity for Q. cyanescens, including antibacterial and antifungal activities (Kuan et al 2015, Stodůlková et al 2015.…”
Section: Ecology and Future Prospectsmentioning
confidence: 99%